1999
DOI: 10.1038/6029
|View full text |Cite
|
Sign up to set email alerts
|

Localization of human BRCA1 and its loss in high-grade, non-inherited breast carcinomas

Abstract: Although the link between the BRCA1 tumour-suppressor gene and hereditary breast and ovarian cancer is established, the role, if any, of BRCA1 in non-familial cancers is unclear. BRCA1 mutations are rare in sporadic cancers, but loss of BRCA1 resulting from reduced expression or incorrect subcellular localization is postulated to be important in non-familial breast and ovarian cancers. Epigenetic loss, however, has not received general acceptance due to controversy regarding the subcellular localization of BRC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
335
3
7

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(368 citation statements)
references
References 23 publications
(22 reference statements)
23
335
3
7
Order By: Relevance
“…Evidence of a role for BRCA1 in sporadic mammary carcinogenesis supports this idea. Thus, BRCA1 expression is decreased or absent in a significant proportion of sporadic breast and ovarian cancer cases, in part because of hypermethylation of the BRCA1 promoter on CpG islands (Wilson et al, 1999;Rice et al, 2000). A significant fraction of sporadic breast cancers (46%) were found to be haploinsufficient for BRCA1 (Staff et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of a role for BRCA1 in sporadic mammary carcinogenesis supports this idea. Thus, BRCA1 expression is decreased or absent in a significant proportion of sporadic breast and ovarian cancer cases, in part because of hypermethylation of the BRCA1 promoter on CpG islands (Wilson et al, 1999;Rice et al, 2000). A significant fraction of sporadic breast cancers (46%) were found to be haploinsufficient for BRCA1 (Staff et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inherited mutations, other means of regulating BRCA1 function may be important in sporadic tumors. The gene is down-regulated at the transcriptional level in sporadic cancer (Catteau et al, 1999;Mancini et al, 1998;Wilson et al, 1999) and the BRCA1 protein becomes mislocalized following infection with certain transforming viruses (Maul et al, 1998). There are currently no models which allow testing for the consequences of individual mutations in the human BRCA1 gene in an intact animal system.…”
Section: Discussionmentioning
confidence: 99%
“…Testis is a site of signi®cant BRCA1 expression (Lane et al, 1995;Scully et al, 1997b) due to a presumed role for the protein in homologous strand exchange (Snouwaert et al, 1999;Zabludo et al, 1996). Antibodies were the generous gift of Drs C Wilson and D Slamon (UCLA School of Medicine, Los Angeles, CA, USA) and have been described elsewhere (Wilson et al, 1997(Wilson et al, , 1999. None of the antibodies used in this experiment cross-reacted with extracts derived from mice.…”
Section: Placement Of a Brcamentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, three strands of evidence confirm our results to be correct and reproducible under different fixation conditions. Previous work has suggested that MS13 staining is predominantly nuclear and represents the full-length protein (Wilson et al, 1999). However, recent immunoblotting data from the same group (http://www.med.ucla.edu/ora/manuscripts.htm) showed MS13 to detect the D11b splice variant in the cytoplasm as well as the full-length BRCA1 species in the nucleus.…”
Section: Discussionmentioning
confidence: 95%